KARAKTERISTIK FISIOLOGI DAN ENERGI SPESIFIK ATLET JUNIOR BULUTANGKIS SAAT PERTANDINGAN - Rachman, Yusniar
Badminton is a very popular sport in Indonesia. It is one of the sports that Indonesia can be proud of. A well-arranged training system can contribute in increasing athletes’ performance. The training system could be arranged based on the intensity and fatigue, both of them have a significant correlation with heart rate and blood lactate concentration. The purposes of this research are to identify the physiological characteristics, dominant metabolic system and analyze the energy expenditure of junior athlete on a badminton matchplay. This research is an observasional study that is done by concurrent method with collecting anthropometry data, measuring VO2max (off the match), monitoring heart rate, measuring blood lactate, distance covered and energy expenditure (on the match). VO2max was measured by Balke test method. Heart rate, distance covered and energy expenditure were measured using Polar® RS400 series device. Blood lactate concentration was measured using Accutrend Plus® device. Sample consists of 9 male semi-professional junior athletes on a province level with range of age between 11-19 years old from a well- known badminton club in Bandung. From the result, mean weight, height, %-body fat, BMI and VO2max in order are 53,31?6,93 kg; 165,67?5,12 cm; 12,66?1,25%; 19,38?1,92 kg/m 2 and 49,29?3,09 mL/kg/menit. Heart rate on matchplay is below the heart rate on Balke test graphically with 81?5% HRmax. There is a significant difference (p<0,05) between blood lactate before and after every match set. Mean distance covered and energy expenditure on matchplay are 2217?792 meters and 378,67?158,51 kkal. Conclusions from the result are 4 out of 9 samples have excellent VO2max and the rest are good. Badminton is a high intensity sport with high demand in individual aerobic capacity. The dominant metabolic system on badminton matchplay is alactic anaerobic system. Energy expenditure have a linear connection with distance covered and %HR max.